What is the role of Semmes-Weinstein monofilament testing in the diagnosis of electrophysiologically graded carpal tunnel syndrome? - GÜNDÜZ, OSMAN HAKAN (SOC PHYSICAL THERAPY SCIENCE, 2015)
[Purpose] The aim of the study was to investigate the ability of Semmes-Weinstein Monofilament testing to detect carpal tunnel syndrome, as well as moderate-to-severe carpal tunnel syndrome using varying thresholds and methods. [Subjects] Clinical and electrophysiological data of 62 patients (124 hands) with a mean age of 49.09+/-10.5 years were evaluated in this study. [Methods] Sensitivity and specificity were calculated according to two threshold values (2.83 and 3.22) and two methods, a conventional method and an internal comparison method. A threshold value of 3.22 was also used to determine sensitivity and specificity in the diagnosis of electrophysiologically moderate-to-severe carpal tunnel syndrome. Data of the first three digits were averaged to reveal the mean strength value of the monofilaments for each hand. [Results] The criteria of 2.83-conventional method yielded a sensitivity of 98% and a specificity of 17% in the diagnosis of carpal tunnel syndrome. The threshold value of 3.22 using a conventional method was found to detect moderate-to-severe carpal tunnel syndrome with high sensitivity (80%) and excellent specificity (93%). A statistically significant difference was observed in the mean strength values of the monofilaments in moderate-to-severe carpal tunnel syndrome hands and hands without carpal tunnel syndrome. [Conclusion] The current study demonstrated that Semmes-Weinstein monofilament testing might be a valuable quantitative method for detecting moderate-to-severe carpal tunnel syndrome.
Keywords: Semmes-Weinstein monofilaments; Sensitivity and specificity; Carpal tunnel syndrome